The activities of the Ukrainian SSR militia in combating crime in the early 1960s. - V. A. Grechenko (Law and Safety)
The article examines the state of crime in the Ukrainian SSR in 1962–1964 and the range of measures taken by the leadership of the Ministry of Public Order and its subdivisions in regions, cities and districts to counteract it. The analysis of statistical data shows that the rate of premeditated murders, dominated by domestic and hooliganism, remained high. Striking were the figures showing a large number of premeditated murders of newborn children, which indicated the low moral level of some Soviet people and their social disadvantage. As in previous years, the militia used mainly operational measures to combat crime, and also carried out some preventive work among the population to identify and verify signals of death threats, as well as criminal intentions and intentions of individual citizens. Given the growth of economic crime, considerable attention was paid to strengthening the agent apparatus, in particular at facilities where large amounts of material assets were concentrated and could be stolen. At the same time, certain mistakes were made and some shortcomings occurred in the course of these activities. In a number of work plans of investigative departments and offices in many regions, many measures were of a general, non-specific nature. One of the significant shortcomings was the planning of activities that were not within the competence of the investigative apparatus of the Ministry of Public Order. Documents from the Investigative Department of the Ministry of Public Order contain many materials about the shortcomings and insufficient competence of investigators in preparing materials sent for forensic biological examination. Among the new manifestations of crime in the analysed years was the phenomenon of theft of narcotic substances from pharmacies and medical institutions, which expanded the range of militia activities. It is noted that in 1962–1964 the militia carried out significant work to combat crime, although it was not always successful.